Ruthenium‐Catalyzed α‐(Hetero)Arylation of Saturated Cyclic Amines: Reaction Scope and Mechanism. Issue 31 (18th June 2013) - Peschiulli, Aldo; Smout, Veerle; Storr, Thomas E.; Mitchell, Emily A.; Eliáš, Zdeněk; Herrebout, Wouter; Berthelot, Didier; Meerpoel, Lieven; Maes, Bert U. W.
Abstract Transition‐metal‐catalyzed sp3 CH activation has emerged as a powerful approach to functionalize saturated cyclic amines. Our group recently disclosed a direct catalytic arylation reaction of piperidines at the α position to the nitrogen atom. 1‐(Pyridin‐2‐yl)piperidine could be smoothly α‐arylated if treated with an arylboronic ester in the presence of a catalytic amount of [Ru3(CO)12] and one equivalent of 3‐ethyl‐3‐pentanol. A systematic study on the substrate and reagent scope of this transformation is disclosed in this paper. The effect of substitution on both the piperidine ring and the arylboronic ester has been investigated. Smaller (pyrrolidine) and larger (azepane) saturated ring systems, as well as benzoannulated derivatives, were found to be compatible substrates with the α‐arylation protocol. The successful use of a variety of heteroarylboronic esters as coupling partners further proved the power of this direct functionalization method. Mechanistic studies have allowed for a better understanding of the catalytic cycle of this remarkable transformation featuring an unprecedented direct transmetalation on a RuIIH species.